Fatal granulomatous amoebic encephalitis due to free‐living amoebae in two boys in two different hospitals in Lima, Perú. Issue 2 (22nd November 2019) - Cabello‐Vílchez, Alfonso Martín; Chura‐Araujo, Miguel A.; Anicama Lima, William E.; Vela, César; Asencio, Angélica Y.; García, Hugo; del Carmen Garaycochea, María; Náquira, César; Rojas, Elvis; Martínez, Dalila Y.
Abstract : Granulomatous amoebic encephalitis caused by free‐living amoebae is a rare condition that is difficult to diagnose and hard to treat, generally being fatal. Anti‐amoebic treatment is often delayed because clinical signs and symptoms may hide the probable causing agent misleading the appropriate diagnostic test. There are four genera of free‐living amoeba associated with human infection, Naegleria, Acanthamoeba sp., Balamuthia and Sappinia . Two boys were admitted with diagnosis of acute encephalitis. The history of having been in contact with swimming pools and rivers, supports the suspicion of an infection due to free‐living amoebae. In both cases a brain biopsy was done, the histology confirmed granulomatous amoebic encephalitis with the presence of amoebic trophozoites.